Current progress of nanotechnology in medicine: application in drug delivery, diagnostic, tissue engineering, and nanobots - Febriofca Galih Yatalaththov; Fadhlurrahman, Ahmad Ghitha; Rahma, Alifia Hetifa; Husna Fitri (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
The integration of nanotechnology into medicine has resulted in rapid advancements, and revolutionized in the diagnosis, treatment and management of diseases. Through complex manipulation of materials at the nanoscale, nanotechnology has ushered in a new era of precision medicine. Their benefits include increasingly in earlier and more precise diagnosis, as well as in optimal treatment of diseases. This review explores the applications of nanotechnology in medicine, with a focus on drug delivery, diagnostic tools, tissue engineering, and the world of futuristic nanorobots. By investigating the complex workings of nanotechnology in medicine, we aim to highlight its innovative applications, the benefits it brings to diagnosis, and treatment, and its potential to reshape the landscape of contemporary medical practice.